Complete chloroplast genome sequence of Camellia rhytidophylla, comparative and phylogenetic analysis. Issue 1 (2nd January 2021) - Liu, Xiao-Fei; Sun, Ying-Bo; Huang, Li-Li; Xu, Ye-Chun; Zhao, Chao-Yi; Yu, Bo
Abstract: Camellia rhytidophylla is an endangered plant with economic value. Using Illumina sequencing, the chloroplast genome of C. rhytidophylla was sequenced and analyzed in this study. The complete chloroplast genome is 157, 073 bp in length, which consisted of a pair of inverted repeat regions of 26, 055 bp (IRa and IRb) separated by a large single-copy region (LSC) of 86, 680 bp and a small single-copy region (SSC) of 18, 283 bp. The C. rhytidophylla chloroplast genome encodes 135 genes, including 87 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 3 pseudogenes. Sequence comparison analysis with the chloroplast sequences of 28 other Camellia plants found that C. rhytidophylla had the closest relationship with C. szechuanensis . This study provides a theoretical basis for the analysis of the distant relationship of Camellia .